Comparison of the Effectiveness of Mindfulness-Based Cognitive Therapy and Acceptance and Commitment Therapy on Intolerance of Uncertainty and Self-Efficacy in Patients with Breast Cancer - Ghafourian, Ghazal; Ghorbani Gherkhloo, Maryam; Siahbazi, Faezeh; Ozbaczaei, Fahimeh; Pourjafar, Fatemeh; Shahbazi, Giti; Pourmohammad Ghouchani, Kamran (Psychology of Woman Journal, 2025)
Objective: This study aimed to compare the effectiveness of Mindfulness-Based Cognitive Therapy (MBCT) and Acceptance and Commitment Therapy (ACT) on pain self-efficacy and intolerance of uncertainty in women diagnosed with breast cancer. Methods and Materials: A quasi-experimental design with a pretest–posttest format and a nonequivalent control group was employed. The statistical population consisted of women with stage 3 and grade 2 breast cancer undergoing chemotherapy at a radiotherapy and oncology center in Tehran during the second half of 2024. A total of 45 participants were selected using convenience sampling and randomly assigned to two experimental groups (MBCT and ACT, 15 each) and one control group (15 participants). The MBCT protocol was implemented over eight weekly sessions based on the Segal et al. (2013) program, while the ACT protocol was based on the model developed by Dahl et al. (2014). Instruments included the Pain Self-Efficacy Questionnaire (Nicholas, 1998) and the Intolerance of Uncertainty Scale (Freeston et al., 1994). Data were analyzed using repeated measures ANOVA and Tukey post hoc tests. Findings: The results of repeated measures ANOVA revealed statistically significant differences among the three groups in both pain self-efficacy (F = 1476.764, p < .001, η² = .946) and intolerance of uncertainty (F = 2511.995, p < .001, η² = .968). Post hoc analyses showed that both MBCT and ACT were significantly more effective than the control group in improving pain self-efficacy and reducing intolerance of uncertainty (p < .01). Furthermore, MBCT and ACT demonstrated differing levels of effectiveness in influencing these outcomes. Conclusion: Both interventions significantly enhance pain self-efficacy and reduce intolerance of uncertainty in women with breast cancer, and may serve as complementary interventions alongside medical treatments.